The properties of plasma-liquid system with one liquid electrode - Nedybaliuk, O.A.; Solomenko, O.V.; Chernyak, V.Ya.; Martysh, E.V.; Fedirchyk, I.I.; Prysiazhnevych, I.V. (Вопросы атомной науки и техники, 2013)
The results of investigations are presented for a rotational gliding arc with liquid electrode. Emission spectra of rotational gliding arc discharge with liquid electrode were investigated. The discharge voltage as a function of airflow rate were measured. Electronic Te*, vibrational Tv* and rotational Tr* temperature were determined. Distribution of temperature along the plasma torch was studied.